2014
DOI: 10.1002/ejp.609
|View full text |Cite
|
Sign up to set email alerts
|

Does pain severity guide selection to multimodal pain rehabilitation across gender?

Abstract: Higher scores on self-reported pain did not guide selection to MMR and a negative trend was found among women. Studies of referral patterns and decision processes may contribute to a better understanding of the clinical practice that decides selection to MMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 45 publications
6
17
1
Order By: Relevance
“…The theme ‘Access to rehab – not a given’ points to participants’ perceptions of rehabilitation as a resource that is not equally available to everyone. This result is congruent with our earlier findings from a register study in the same setting (19, 20, 36). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The theme ‘Access to rehab – not a given’ points to participants’ perceptions of rehabilitation as a resource that is not equally available to everyone. This result is congruent with our earlier findings from a register study in the same setting (19, 20, 36). …”
Section: Discussionsupporting
confidence: 93%
“…When identifying inequities in health care and rehabilitation, it is thus crucial to be aware of the intersection of social categories and constructions. Using a tool that addresses gender inequality, and intersecting social aspects, in daily clinical work may be one way of raising awareness (36). The tool can be included in clinical assessment of patients and as an instrument for critical reflection on gender bias during health professional team education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Is looks as if the needs of the males and female in general are different. Further research is needed in order to investigate to what extent the differences we found are due to disparities in assessment modalities, practitioners’ attitude or referral patterns, knowledge and/or stigmatization that the patient has met before [78] or after referral [4]. …”
Section: Discussionmentioning
confidence: 99%
“…The main questions evolved from the discussions, enabling both the moderator and the participants, the flexibility to probe for details. The discussion outline was based on the international literature pertinent to pain management, nurses, and patients' characteristics (Dijk et al, ; Etherton, Lawson, & Graham, ; Haukenes, Hensing, Stålnacke, & Hammarström, ). The discussion outline included four broad questions:
Do you think that patients' characteristics affect your decision in pain management?
…”
Section: Methodsmentioning
confidence: 99%